Utilization of Google Class Room in improving learning quality for lecturers and students at the USU department of biology FMIPA - Rahayu, Suci; Pasaribu, Nursahara; Elimasni; Sabri, Emita; Supriharti, Denny (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2019)
Community service activities titled Transforming Organic Waste into Organic Fertilizer in Namo Bintang Village in May - November 2019. This activity aims to convert organic waste into organic fertilizer that has economic value, and does not endanger the environment. The method used is counseling, lectures and training as well as monitoring and evaluation with the community directly to the field. Utilization of Google Class Room is done in several places in the Biology department with the approval of the Chair of the Department. The activity was carried out by means of counseling and lectures, explaining the theory and techniques of using Google Class Room, which was followed by a group of Lecturers and Students in the Biology department at USU FMIPA.The training was conducted by a group of Lecturers and Students in the Biology department of USU FMIPA separately. All carry out this activity by proactively conducting training to get results in the form of the Google Class Room application. The equipment for using Google Class Room is only a laptop, smartphone and internet package. And finally the monitoring and evaluation of the success of monitoring work in the field will be carried out by going directly to the field together, monitoring by visiting to find out whether lecturers and students have been able to do it themselves. In addition, the relationship will be carried out by telephone to overcome the problems that arise . In general, community service activities have been successfully carried out and seen a good cooperative relationship between the Higher Education, especially the Implementation Team, the village community realizes the importance of saving the environment from at the same time improving life expectancy because it can make its own fertilizer / compost.